The Muslim Social Integration Within Different Social Groups in Indonesia: The Dynamics of Their Horizontal Integration in Pre-independence Period - Sukron Kamil (UIN Sunan Gunung Djati Bandung, 2023)
One of the social problems that is now emerging in Indonesia is the decline of Muslim social integration. This article wants to discuss the Muslim social integration within different social groups in Indonesia in the pre-independence period in order to become an example for Muslim integration today. The method used in writing is a literature-based qualitative research method, with a theoretical approach to Muslim social integration with non-Muslim communities. This article finds that, in the perspective of horizontal integration, Indonesian Muslim societies generally integrate with different communities, varying ethnicity, race, socio-political and economic interests, especially with different religions. And this is the reality of mainstream social in Indonesia at the pre-colonial period and the colonial period. However, the Muslim social integrity, can not be called an absolute social reality. The Muslim horizontal social integration in Indonesia is dynamic. The social integration of Muslims in Indonesia with different societies is also not an independent entity.